Continuous monitoring for leaching of calcium sulfoaluminate cement pastes incorporated with ZnCl2 under the attacks of chloride and sulfate. (May 2019) - Tang, Shengwen; Yuan, Junhui; Cai, Rongjin; Wei, Xuanchun; Zhao, Cheng; Cai, Xinhua; He, Zhen; Chen, E.
Abstract: Ionic zinc is considered as an environmental pollutant. This work systematically investigated leaching mechanisms of calcium sulfoaluminate cement (CSA) pastes incorporated with/without ZnCl2 under the attacks of chloride and/or sulfate. The leaching behaviors of CSA pastes in the leaching solution are in-situ and continuously monitored by innovative non-contact electrical impedance measurement (NCEIM) and pH meter. The dissolution and diffusion during the leaching process are experimentally identified. Other techniques are also performed to verify the finding of NCEIM: the ion chromatograph and inductively coupled plasma optical emission spectrometer reveal the leaching or decomposition sequence of CSA pastes during the leaching process. Besides, results from XRD and SEM techniques demonstrate that main solid products in CSA pastes are ettringite and calcium monosulfoaluminate hydrates. The incorporation of Zn in the pastes has great impact on the decomposition of CSA pastes in the temperature elevation. External chloride and/or sulfate attacks significantly alter the pore structure of CSA pastes during the leaching process. Highlights: Leaching behaviors of CSA pastes are characterized by innovative impedance method. Leaching or decomposition sequence of CSA pastes is studied. The incorporation of Zn affects pore structure and decomposition of CSA pastes.